EKSPEKTASI DAN TINGKAT KEPUASAN PRAJA TERHADAP KUALITAS PELAYANAN LEMBAGA PENDIDIKAN DI IPDN KAMPUS SULAWESI UTARA - Hestiwaty Basir (Institut Pemerintahan Dalam Negeri, 2017)
This journal entitled “Expectation and Level of Satisfaction of Teachers on Quality of Services Educational Institutions at IPDN of North Sulawesi Campus” aims to know how the level of satisfaction of praja to Quality of Services Educational Institutions in IPDN Kampus Sulut in terms of reliability (Reability), Responsiveness, Assurance, (Emphaty), and Tangibles (Tangibles), to find out whether there is a difference between expectations and perceptions of the quality of services educational institutions in IPDN Kampus Sulut in terms of EDUQUAL instruments and to know how to improve the satisfaction of Praja on the quality of services educational institutions in IPDN North Sulawesi Campus. IPDN North Sulawesi Campus is one of the local campus that currently educates 322 people of praja, in order to produce a quality and ready-made praja required the commitment and effort in the implementation of all campus activities, especially in providing quality services for praja. The findings of this study conclude that partially and simultaneously dimensions of service quality reability, responsiveness, assurance, emphaty and tangibles provided by IPDN Educational Institution in North Sulawesi Campus have a positive and significant effect. This research also findings that IPDN Educational Institution in North Sulawesi Campus has not fully satisfy Praja, because consumer expectation value is still higher than service given. There needs to be a strategy to increase the satisfaction of the services according to the priority of the services needed. Keywords: EDUQUAL instrument, commitment